Penentuan Kebijakan Pemenuhan Pesanan Dengan Model Vendor-Managed Inventory - Sri Hartini; Andrie Mustafa Kamal (Jurnal Teknik Industri, 2010)
Rapid development in Manufacturing field and in information is more sophisticated now. Here to this can help the manufacturer in developing supply chain management and building better cooperation between parties such as distributor, supplier, and  consumer. There is a policy which is using this technology known Vendor Managed Inventory (VMI). With this policy manufacturer can give responsibility to the supplier for managing and  determining when and how much the product will be delivered according to inventory and demand in that time. PT Sampharindo Perdana is a company in pharmaceutical. Today this company manufactures 88 medicine consist of capsule, pill, syrup, and drops. The problem faced by this Company is orderchanging from distributor. So that, if it is happen very often it can make lateness and cancel the orders. Avoiding from that problem, we can use VMI policy with LRP logics as a tools of detemining when and how much delivery will be carried on to the distributor. From this policy we will get a policy to determine when and how much delivery will be carried on to the distributor.This policy can minimize average inventory to 8% and enhance service level up to 4%.